Mepolizumab targets multiple immune cells in aspirin-exacerbated respiratory disease - Buchheit, Kathleen M.; Lewis, Erin; Gakpo, Deborah; Hacker, Jonathan; Sohail, Aaqib; Taliaferro, Faith; Berreondo Giron, Evans; Asare, Chelsea; Vukovic, Marko; Bensko, Jillian C.; Dwyer, Daniel F.; Shalek, Alex K.; et al. (Journal of allergy and clinical immunology, 2021)
Eosinophilic asthma and nasal polyposis are hallmarks of aspirin-exacerbated respiratory disease (AERD), and IL-5 inhibition has been shown to provide therapeutic benefit. However, IL-5Rα is expressed on many cells in addition to eosinophils, and the mechanisms by which IL-5 inhibition leads to clinical benefit in eosinophilic asthma and nasal polyposis are unlikely to be due exclusively to antieosinophil effects. We sought to identify the mechanisms by which anti–IL-5 treatment with mepolizumab improves respiratory inflammation in AERD. The clinical characteristics, circulating granulocytes, nasal scraping transcripts, eosinophilic cationic protein, tryptase, and antibody levels, and urinary and nasal eicosanoid levels were measured for 18 subjects with AERD who were taking mepolizumab and compared with those of 18 matched subjects with AERD who were not taking mepolizumab. Subjects taking mepolizumab had significantly fewer peripheral blood eosinophils and basophils, and those cells that remained had higher surface CRTH2 expression than did the cells from subjects not taking mepolizumab. Nasal prostaglandin F2α, prostaglandin D2 metabolites, leukotriene B4, and thromboxane levels were lower in subjects taking mepolizumab, as were urinary levels of tetranor–prostaglandin D2 and leukotriene E4. The nasal epithelial cell transcripts that were overexpressed among subjects with AERD who were taking mepolizumab were enriched for genes involved in tight junction formation and cilium organization. Nasal and urinary prostaglandin E2, tryptase, and antibody levels were not different between the 2 groups. IL-5 inhibition in AERD decreases production of inflammatory eicosanoids and upregulates tight junction–associated nasal epithelial cell transcripts, likely due to decreased IL-5 signaling on tissue mast cells, eosinophils, and epithelial cells. These direct effects on multiple relevant immune cells contribute to the mechanism of benefit afforded by mepolizumab. [Display omitted]